Pengurusan Perpustakaan muslim abad ke 8-19 masihi: Satu pengenalan - Tamjehi, Haslan; Ramli, Latifah (Persatuan Pustakawan Malaysia, 2015)
Muslim libraries have undergo a long comprehensive history. Its existence which began since 6th century A.D. are recorded in written sources by Muslims and orientalists. Some of the sources are preserved till today as precious knowledge and intellectual heritage of the human civilization. Hence, this writing introduces the unique aspects of Muslim libraries during Islamic period until 19th century A.D. such as collection development, cataloging and circulation. The details of those aspects will be illustrated to understand its management within the specified period.